Maintenance access in high rise building / Nurul Izza Mansor - Mansor, Nurul Izza (Faculty of Architecture, Planning and Surveying, 2009)
What is building? Although this might at first sight appear to be a relatively straightforward question, it can nevertheless be answered in a variety of ways. Building is a shelter to give a protection for the human. Building has provided services to give comfort ability and also have a user needs characteristic. An access for maintenance is vital in the maintenance of any building. Nowadays, all the buildings require maintenance to keep good of the systems. Access is one of the basic requirements before the personnel could start their working. The research discusses on method of access for maintenance and the identification of the problem arises in the access available in the building. This research has chosen high-rise buildings as a case study: 1. Tabung Haji Headquarters (TH HQ) 2. P.N.B Tower 3. MARA Headquaters (MARA HQ)